Reduction of Interhemispheric Homotopic Connectivity in Cognitive and Visual Information Processing Pathways in Patients With Thyroid-Associated Ophthalmopathy - Qi, Chen-Xing; Wen, Zhi; Huang, Xin (Frontiers in Human Neuroscience, 2022)
Purpose: Thyroid-associated ophthalmopathy (TAO) is a vision threatening autoimmune and inflammatory orbital disease, and has been reported to be associated with structural and functional abnormalities of bilateral hemispheres. However, whether the interhemisphere functional connectivity of TAO patients is altered still remain unclear. A new technique called voxel-mirrored homotopic connectivity (VMHC) was used in the present study to explore inter-hemispheric homotopic functional connectivity alterations in patients with TAO. Methods: A total of twenty-one TAO patients (14 males and 7 females) and twenty-one well-matched healthy controls (HCs, 14 males and 7 females), respectively, underwent functional magnetic resonance imaging (fMRI) scanning in the resting state. We evaluated alterations in the resting state functional connectivity between hemispheres by applying the voxel-mirrored homotopic connectivity (VMHC) method and then selected these abnormal brain regions as seed areas for subsequent study using functional connectivity (FC). Furthermore, the observed changes of regions in the VMHC analysis were chosen as classification features to differentiate patients with TAO from HCs through support vector machine (SVM) method. Results: The results showed that compared with HCs, TAO patients showed significantly lower VMHC values in the bilateral postcentral gyrus, lingual gyrus, calcarine, middle temporal gyrus, middle occipital gyrus and angular. Moreover, significantly decreased FC values were found between the right postcentral gyrus/lingual gyrus/calcarine and left lingual gyrus/cuneus/superior occipital gyrus, left postcentral gyrus/lingual gyrus/calcarine and right lingual gyrus/ middle temporal gyrus, right middle temporal gyrus and left cerebellum-8/lingual gyrus/middle occipital gyrus/supplementary motor area, left middle temporal gyrus/angular and right middle occipital gyrus, right middle occipital gyrus/angular and left middle temporal pole (voxel-level p<0.01, Gaussian random field correction, cluster-level p<0.05). The SVM classification model achieved good performance in differentiating TAO patients from HCs (total accuracy: 73.81%; area under the curve: 0.79). Conclusion: The present study revealed that the altered interhemisphere interaction and integration of information involved in cognitive and visual information processing pathways including the postcentral gyrus, cuneus, cerebellum, angular, widespread visual cortex and temporal cortex in patients with TAO relative to HC group. The new findings may provide novel insights into the neurological mechanisms underlying visual and cognitive disorders in patients with TAO.